Stock Split Announcement And Market Reaction: Evidence From Pt Hillcon Tbk - A. Reski Almaida Dg Macenning (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study aims to analyze the market reaction to the announcement of the stock split by PT Hillcon Tbk in March 2025 using the event study approach. The observation period covers a 21-day event window, 10 days before and 10 days after the announcement, with an estimation period of 74 days prior to the event window. Market reaction measurements include abnormal return (AR), average abnormal return (AAR), cumulative abnormal return (CAR), and trading volume activity (TVA). The results show significant market reactions characterized by increases in AAR and trading volume activity, supported by the Wilcoxon signed-rank test. Although there was a short-term decline following the announcement, overall the stock split provided positive signals and increased the liquidity of PT Hillcon’s shares. These findings reinforce the signaling theory and liquidity hypothesis while providing empirical contributions to the understanding of semi-strong form market efficiency in Indonesia. This study highlights how stock splits can positively influence investor behavior by enhancing stock liquidity and signaling firm value. The significant abnormal returns and trading volume changes reflect investors’ sensitivity to corporate actions in emerging markets like Indonesia. The use of a 21-day event window provides a comprehensive view of the immediate market response around the announcement date. This research offers valuable insights for corporate managers and investors regarding the timing and expected impact of stock splits, emphasizing the importance of transparent communication and market efficiency considerations.